The Effect of Proprioception Exercises on the Risk of Fall in Knee Osteoarthritis - Ali Hakan Aydemir; Ömer Faruk Şendur; Gülnur Taşcı Bozbaş (Galenos Yayinevi, 2017)
Objective: The aim of this study was to investigate the effect of proprioception exercises on the risk of fall in primary knee osteoarthritis patients. Materials and Methods: Patients diagnosed with knee osteoarthritis according to the American College of Rheumatology criteria were evaluated among the patients who applied to the outpatient clinic. Among them fifty patients (38 female and 12 male) who were graded as phase 2 or 3 according to Kellgren-Lawrence criteria were included in this study. Proprioception exercises were performed to patients for 10 days in company with physiotherapists. Thereafter patients were given a 6 months of home exercise program. The risk of fall in patients with knee osteoarthritis was assessed by Tetra-axiometric posturographic device (Tetrax, Sunlight Medical Ltd, Israel) that measures in 8 different positions. Functional status was assessed by Lequesne index and pain intensity by visual analogue scale (VAS). The assessments were made in the beginning, on the 15th day and in 1st, 3rd and 6th month. Results: The mean age of the patients was 58.78±7.83 year. A statistically significant improvement in the risk of falls, VAS score and Lequesne index was determined in the first assessment on 15th day after proprioceptive exercises (p<0.001). In the assessment in 6th month, it was observed that this improvement increasingly continued. Conclusion: At the present time, the falls are of great importance due to their medical and economic consequences. At the same time it is known that knee osteoarthritis increases the risk of falls. According to the results of our study, we think that proprioceptive training in the treatment of patients with knee osteoarthritis may provide important contributions both in reducing the risk of falls and in improving functional status.